Non-specific low back pain – what does it exactly mean? A proposed redefinition and classification of the problem - Małecki, Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Introduction. Analysis of the medical literature shows that non-specific low back pain is a multifaceted affliction. Determining the unequivocal definition and classification of the ailment could be somewhat difficult. The following review presents a multiplicity of common low back pain nuances. The paper also shows necessity of unification of the definition and clarification, for placing non-specific low back pain among other musculoskeletal disorders. Aim. The author will attempt to provide the answers to basic questions about non-specific low back pain. In its form, the paper will have similarities to the prospect study with narrative review features. Although the reader should remember that the article is neither a result of expert team efforts nor non-specific low back pain leading authority opinion. Therefore the suggestions should be interpreted with necessary distance and scientific scepticism. Material and methods. Proper publications were searched in PubMed and EBSCO scientific articles databases, using terms: ‘nonspecific low back pain’ or ‘non-specific low back pain’, ‘definition’, ‘diagnostic triage’, and ‘classification’ in different combinations. Results. As a result of the review, subtle correction of the current non-specific low back pain definition has been proposed. Acknowledgments. The author of this review wishes to show his appreciation to Prof. Edward Saulicz, the promotor and mentor for didactic support, methodologic and merythoric advice, and for manuscript correction. Thanks also extended to colleague Łukasz Sejboth, master of physiotherapy, for help with appropriate references and motivation to scientific exploration with his unassailable attitude and professionalism. Furthermore, author would like to acknowledge Keith Littlewood for his kind and valid amendments in the English version of the manuscript.
Keywords: low back pain; classification; triage; syndrome